Analisis NRW pada Perumda Air Minum Tirta Mangutama Kabupaten Badung - I Wayan Adi Sudiatmika (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2023)
The percentage of Non-Revenue Water (NRW) at PAM Tirta Mangutama from 2016–2021 is far above the maximum tolerance of 20% and even tends to increase every year. The increasing percentage of NRW causes the performance of PAM Tirta Mangutama to decline. The increase in the percentage of NRW causes a decrease in water pressure at the customer, discontinuity of service to customers, low service coverage, and lower income for PAM Tirta Mangutama. For this reason, research was carried out using the administrative product compilation method and descriptive analysis was carried out. The study was carried out in order to identify the causes of the high percentage of NRW and to provide recommendations for policies and appropriate strategies for PAM Tirta Mangutama Badung Regency in order to control the high level of water loss. In 2020 and 2021, the cost of water with real NRW will be higher than the cost of water in effect at that time, so that in 2020 and 2021 PAM Tirta Mangutama cannot meet the full cost (unfull cost recovery). Based on the water balance in 2021, non-physical and physical water losses are far greater than water losses based on unbilled official consumption. Efforts to suppress the high percentage of NRW require strategic steps that are grouped into 3 programs, namely: short-term, medium-term, and long-term programs.